Rethinking Teacher Professional Development for the Digital Era: A Narrative Review - Anisah, Ani Siti; Masripah; Putri, Mentari Juanda (Eduscape : Journal of Education Insight, 2025)
This narrative review examines teacher professional development (TPD) in the digital age, particularly following the acceleration of digitalization during the COVID-19 pandemic. The study analyzes best practices, challenges, and strategies for effective TPD. Literature was collected from Scopus, Web of Science, and Google Scholar using keywords such as teacher professional development, technology integration, artificial intelligence in education, blended learning, and the TPACK framework. Inclusion criteria covered peer-reviewed studies from 2010 to 2025 focusing on digital competencies, pedagogical integration, and professional training outcomes. Findings highlight four themes: technology integration that enhances pedagogy and student outcomes; collaboration through professional learning communities that strengthen engagement; inequities in access and readiness, especially between urban and rural teachers; and ethical concerns, including professional identity in AI adoption. Systemic factors such as infrastructure, policies, and institutional culture strongly influence effectiveness. Although digital tools provide clear benefits, their potential is limited without supportive ecosystems. The discussion emphasizes sustainable, context-relevant training, collaborative environments, equitable access, and embedding ethics in TPD. Future research should prioritize longitudinal studies to assess long-term impacts. Overall, effective TPD is crucial for fostering inclusive, innovative, and ethically grounded education in the digital era.